The Need to Investigate the Five-Year Impact of Covid-19 on Student Online Feedback for Course X - Soffian Noor Mat Saliah; Noorsuhada Md Nor; Roziah Keria; Abdullahi Nafiu Zadawa (Penerbit Universiti Kebangsaan Malaysia, 2025)
This paper presents the investigation of student online feedback (SUFO) for Course X of the Civil Engineering degree programme over five years in relation to before, during and after Covid-19. Several approaches to student feedback were conducted focusing on the students of semesters 20192, 20194, 20202, 20204, 20212, 20214, 20222, 20224, 20232 and 20234. The study only refers to the specific Course X. The parameters for student feedback were the students’ overall impression of course X, the professionalism of the lecturers, the teaching and learning activities and the infrastructure. The study shows that the transition from physical to online courses has led to a decline in all parameters assessed, especially in the 2019 semester 4, indicating a signifi cant negative impact of the switch to online learning on students’ perception of Course X in the Civil Engineering programme.